2020
DOI: 10.21203/rs.2.23352/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hydrogen rich water ameliorate Trimethyltin induced spatial learning and memory impairment by regulation of Siah-1

Abstract: Background: As an important member of organic tin compounds, Trimethyltin (TMT) exists widely in industrial and agricultural productions. TMT can induce significant neurodegeneration in the limbic system, particular in hippocampus. However, the molecular mechanisms in TMT-induced learning and memory impairment are not fully clear. Thus, this research was to explore the role of Synaptophysin (SYP) and Ubiquitin-ligating enzyme Siah-1 in TMT-induced nerve impairment and the protective effect of hydrogen rich wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…A study conducted by Park et al, reported that TMT induction increased the p-tau expression in TMT-induced mice [67]. Accordingly, a previous conducted a study on H 2 showed amelioration of TMT-induced spatial learning and memory impairment in mice by regulation of Siah-1 [36]. In the present study, we evaluated the cognitive improvement effects of H 2 in TMT-induced mice by measuring the Apo-E levels in the blood and brain.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…A study conducted by Park et al, reported that TMT induction increased the p-tau expression in TMT-induced mice [67]. Accordingly, a previous conducted a study on H 2 showed amelioration of TMT-induced spatial learning and memory impairment in mice by regulation of Siah-1 [36]. In the present study, we evaluated the cognitive improvement effects of H 2 in TMT-induced mice by measuring the Apo-E levels in the blood and brain.…”
Section: Discussionmentioning
confidence: 76%
“…In addition, Iuchi and colleagues demonstrated that administration of H 2 (approximately 1%, v/v) modulated the Ca 2+ signal and modified the generation of oxidized phospholipid species [35]. Recently, Zhou and colleagues reported that hydrogen-rich water has potential to ameliorate TMT-induced memory impairment by regulating Siah E3 ubiquitin protein ligase 1 [36]. However, the therapeutic effects of H 2 on chemically induced neurodegenerative diseases model such as the TMT-induced animal model are poorly studied.…”
Section: Introductionmentioning
confidence: 99%